Becoming friends or foes? How competitive environments shape social preferences - Eugen Dimant; Kyle Hyndmann (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
We study the interaction between competition and social proximity on altruism, trust, and reciprocity. We decompose the behavioral channels by utilizing variants of both the Trust Game and the Dictator Game in a design that systematically controls the transmission of relevant information. Our results suggest that competitive environments, and in particular the outcomes thereof when competitors are socially proximate, affect social preferences. Within the context of the Trust Game, we find that winning makes individuals more trusting, less reciprocal, and less altruistic. In order to decompose the underlying mechanism of decision-makers, we subsequently use the Dictator Game and find that knowledge about winning the competition decreases giving, especially with increased proximity between competitors. From this we can conclude that the observed increase in trust is guided by self-serving concerns to maximize the total pie rather than altruistic concerns to compensate the competitor who lost the competition. Our results provide helpful insights into the structure of incentives within institutions and companies, which is known to affect performance.
Keywords: C9; D01; D6; D9; 330; Altruism; Competition; Reciprocity; Social Proximity; Trust